1990
DOI: 10.1139/v90-309
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of podophyllotoxin analogs

Abstract: Two analogs of podophyllotoxin, with the same absolute stereochemistry as the natural product, have been synthesized from the cycloadduct between a-hydroxy-a'-phenyl-o-quinodirnethane and the furnarate of S-methyl lactate. After initial attempts to produce the cycloadduct from photochemically generated a-hydroxy-a'-phenyl-o-quinodirnethane failed, a study of the thermal generation and reaction of a-hydroxy-o-quinodirnethane with the fumarate and acrylate of S-methyl lactate was made. A comparison was made of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…For all cycloadducts H1 appear between 4.6 and 5.2 ppm (in CDCl,) and endo (cis-1,2) coupling constants, J,,, are 2-5 Hz, while exo (trans-1,2) coupling constants are 7-12 Hz (for previous examples see refs. [2][3][4][5][6]17). The results of the product study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all cycloadducts H1 appear between 4.6 and 5.2 ppm (in CDCl,) and endo (cis-1,2) coupling constants, J,,, are 2-5 Hz, while exo (trans-1,2) coupling constants are 7-12 Hz (for previous examples see refs. [2][3][4][5][6]17). The results of the product study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We recently published several accounts of the stereoselective and asymmetric Diels-Alder reactions of a-hydroxy-ortho-quinodimethanes (a-hydroxy-o-QDMs) with the fumarate of methyl lactate or methyl mandelate (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) www.intechopen.com d6): A Diels-Alder cycloaddition between the fumarate of methyl ( S )-mandelate (46) and α-hydroxy-α'-aryl-o-quinodimethane (45) gives optically pure (-)-α-dimethylretrodendrin (47) having a 1,2-trans-2,3-trans stereochemistry, and three of its diastereomers (Scheme 13) (Charlton et al, 1990), (Charlton & Koh, 1992), (Maddaford & Charlton, 1993). …”
Section: A) C-ring Formation By Aryl Substitutionmentioning
confidence: 99%
“…± We recently presented the complete p-facial selectivity observed in the TiCl 4 -catalyzed [4 2] cycloaddition of cyclopentadiene to N,N'-fumaroylbis[(2R )-bornane-10,2-sultam] ((À)-1a) [1] under the influence of diverse Lewis acids, as well as its application to diverse dienes [2]. Although these kinds of cycloadducts have been employed for the synthesis of several natural products [3] and analogues [4], their use is usually limited to symmetric or specific targets where the two carbonyl moieties can be distinguished by either iodolactonization [5] or selective steric approach of the reagent 3 ). For this reason, nonsymmetrical chiral fumarates were earlier developed [9] 4 ), where one carbonyl moiety may be chemoselectively transposed into a suitable functionality, either by selective saponification [9b], acidic hydrolysis [12], hydrogenation [13], or hydride reduction [14] 5 ).…”
mentioning
confidence: 99%